Multimedia English Teaching Approach Based on Constructivist Learning Theory - Sasan, John Michael Villagorda; Rabillas, Annabelle (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2022)
In the context of English study, multimedia has provided learners with unique features and benefits. Constructivist learning theory, on the other hand, has had a considerable impact on students' learning processes and progress as one of the most fundamental teaching theories in the field of education. This study looks at a wide range of sources to support the claim that integrating multimedia and constructivism theory improved students' overall English learning experience. While the authors of this study thought it would help students improve their English learning, they also wanted to give teachers a better method to help them reduce stress in the classroom while still providing an effective teaching-learning process.